# Math Homework Help

We’ve answered 287,306 questions. We can answer yours, too.

### Showing All Questions Answered Popular Recommended Unanswered Editor's Choice in Math

• Math
`f''(t)=2e^t+3sin(t)` `f'(t)=int(2e^t+3sin(t))dt` `f'(t)=2e^t-3cos(t)+C_1` `f(t)=int(2e^t-3cos(t)+C_1)dt` `f(t)=2e^t-3sin(t)+C_1t+C_2` Now let's find constants C_1 and C_2 , given f(0)=0 and...

Asked by enotes on via web

• Math
`f''(x)=2/3x^(2/3)` `f'(x)=int2/3x^(2/3)dx` `f'(x)=2/3(x^(2/3+1)/(2/3+1))+c_1` `f'(x)=(2/3)(3/5)x^(5/3)+c_1` `f'(x)=2/5x^(5/3)+c_1` c_1 is constant `f(x)=int(2/5x^(5/3)+c_1)dx`...

Asked by enotes on via web

• Math
You need to evaluate f, knowing the second derivative, hence, you need to use the following principle, such that: `int f''(x)dx = f'(x) + c` `int f'(x) dx = f(x) + c` Hence, you need to evaluate...

Asked by enotes on via web

• Math
`f'''(t)=cos(t)` `f''(t)=intf'''(t)dt` `f''(t)=intcos(t)dt` `f''(t)=sin(t)+c_1` `f'(t)=int(sin(t)+c_1)dt` `f'(t)=-cos(t)+c_1t+c_2` `f(t)=intf'(t)dt` `f(t)=int(-cos(t)+c_1t+c_2)dt` `...

Asked by enotes on via web

• Math
`f'''(t)=e^t+t^(-4).` Integrate this once: `f''(t)=e^t+(-1/3)t^(-3)+C_1,` twice: `f'(t)=e^t+(-1/2)(-1/3)t^(-2)+C_1t+C_2,` thrice: `f(t)=e^t+(-1/1)(-1/2)(-1/3)t^(-1)+C_1t^2+C_2t+C_3=...

Asked by enotes on via web

• Math
`f'(x)=1+3sqrt(x)` `f(x)=int(1+3sqrt(x))dx` `f(x)=x+3(x^(1/2+1)/(1/2+1))+c` `f(x)=x+3(x^(3/2)/(3/2))+c` `f(x)=x+3(2/3)x^(3/2)+c` `f(x)=x+2x^(3/2)+c` Now let's find constant c , given f(4)=25...

Asked by enotes on via web

• Math
You need to evaluate f and the problem provides f'(x), hence, you need to use the following relation, such that: `int f'(x)dx = f(x)+ c` `int (5x^4 - 3x^2 + 4)dx = f(x) + c` You need to evaluate...

Asked by enotes on via web

• Math
The general antiderivative of f' is `f(t)=4arctan(t)+C,` where C is any constant. It must be f(1)=0, so C=-4arctan(1). acrctan(1) is `pi/4,` so the answer is `f(t)=4arctan(t)-pi.`

Asked by enotes on via web

• Math
Integrating gives `f(t)=t^2/2-(1/2)t^(-2)+C,` where C is any constant. `f(1)=1/2-1/2+C=C=6,` so C=6. The answer: `f(t)=t^2/2-1/(2t^2)+6.`

Asked by enotes on via web

• Math
You need to evaluate the antiderivative of the function f'(t), such that: `int f'(t)dt = f(t) + c` `int (2cos t + sec^2 t) dt = int 2cos t dt + int sec^2 t dt` `int (2cos t + sec^2 t) dt = 2sin t +...

Asked by enotes on via web

• Math
You need to evaluate the antiderivative of the function f'(x), such that: `int f'(x)dx = f(x) + c` `int (x^2-1)/x dx = int x^2/x dx - int 1/x dx` `int (x^2-1)/x dx = int x dx - int 1/x dx` `int...

Asked by enotes on via web

• Math
You need to evaluate f and the problem provides f'(x), hence, you need to use the following relation, such that: `int f'(x)dx = f(x)+ c` You need to evaluate the indefinite integral of the power...

Asked by enotes on via web

• Math
`f'(x)=4/sqrt(1-x^2)` `f(x)=int(4/sqrt(1-x^2))dx` `f(x)=4arcsin(x)+c_1` Let's find constant c_1 , given f(1/2)=1 `f(1/2)=1=4arcsin(1/2)+c_1` `1=4(pi/6)+c_1` `c_1=1-(2pi)/3`...

Asked by enotes on via web

• Math
`f''(x)=-2+12x-12x^2` `f'(x)=int(-2+12x-12x^2)dx` `f'(x)=-2x+12(x^2/2)-12(x^3/3)+c_1` `f'(x)=-2x+6x^2-4x^3+c_1` Now let's find constant c_1 , given f'(0)=12 `f'(0)=12=-2(0)+6(0^2)-4(0^3)+c_1`...

Asked by enotes on via web

• Math
`f''(x)=8x^3+5` `f'(x)=int(8x^3+5)dx` `f'(x)=8(x^4/4)+5x+c_1` `f'(x)=2x^4+5x+c_1` Now let's find constant c_1 , given f'(1)=8 `f'(1)=8=2(1)^4+5(1)+c_1` `8=2+5+c_1` `c_1=1` `:.f'(x)=2x^4+5x+1`...

Asked by enotes on via web

• Math
`f(x) =1/5-2/x` To determine the most general antiderivative of this function, take the integral of it. `F(x)=int f(x)dx = int(1/5-2/x)dx` Then, apply the integral formula `int cdu=cu +C` and `int...

Asked by enotes on via web

• Math
The most general antiderivative F(t) of the function f(t) can be found using the following relation: `int f(t)dt = F(t) + c` `int (3t^4 - t^3 + 6t^2)/(t^4)dt = int (3t^4)/(t^4)dt - int...

Asked by enotes on via web

• Math
The most general antiderivative G(t) of the function g(t) can be found using the following relation: `int g(t)dt = G(t) + c` `int (1 + t + t^2)/(sqrt t)dt = int (1)/(sqrt t)dt + int (t)/(sqrt t)dt...

Asked by enotes on via web

• Math
The most general antiderivative `R(theta)` of the function `r(theta)` can be found using the following relation: `int r(theta)d theta = R(theta) + c` `int (sec theta*tan theta - 2 e^theta)d theta =...

Asked by enotes on via web

• Math
The most general antiderivative `H(theta)` of the function `h(theta)` can be found using the following relation: `int h(theta)d theta = H(theta) + c` `int (2sin theta - sec^2 theta)d theta = int...

Asked by enotes on via web

• Math
`int f(t) dt=int sin(t)+2 sinh(t) dt = int sin(t) dt + 2 int sinh(t) dt ` We note that the derivative of `cosh(t)=sinh(t) =>d/dx cosh(t) = sinh(t)=>d/dx sinh(t)=cosh(t)` This means that `int...

Asked by enotes on via web

• Math
Integrating f gives (both integrals are well-known) `5e^x-3sinh(x)+C,` where `C` is any constant. This is the answer. Checking by differentiation:...

Asked by enotes on via web

• Math
You need to evaluate the most general antiderivative, using the following rule, such that: `int f(x) dx = F(x) + c` `int (2sqrtx + 6cos x) dx = int 2sqrt x dx + int 6cos x dx` `int (2sqrtx + 6cos...

Asked by enotes on via web

• Math
You need to evaluate the most general antiderivative, using the following rule, such that: `int f(x) dx = F(x) + c` `int (x^5 - x^3 + 2x)/(x^4) dx = int(x^5)/(x^4) dx - int (x^3)/(x^4)dx + int...

Asked by enotes on via web

• Math
You need to evaluate the most general antiderivative, using the following rule, such that: `int f(x) dx = F(x) + c` `int (2 +x^2)/(1+x^2) dx = int(1+x^2)/(1+x^2) dx + int 1/(1+x^2)dx ` `int (2...

Asked by enotes on via web

• Math
You need to evaluate the antiderivative F,under the given condition, such that: `int f(x)dx = F(x) + c` Hence, you need to evaluate the indefinite integral of function f(x), such that: `int (5x^4 -...

Asked by enotes on via web

• Math
`f(x)=4-3(1+x^2)^-1` `F=int(4-3(1+x^2)^-1)dx` `F=int4dx-int3/(1+x^2)dx` `F=4x-3arctan(x)+c_1` Let's find constant c_1 , given F(1)=0 `F(1)=0=4(1)-3arctan(1)+c_1` `0=4-3(pi/4)+c_1` `c_1=(3pi)/4-4`...

Asked by enotes on via web

• Math
`f''(x)=20x^3-12x^2+6x` `f'(x)=int(20x^3-12x^2+6x)dx` Applying the sum rule and power yields, `f'(x)=20(x^4/4)-12x^3/3+6x^2/2+c_1` `f'(x)=5x^4-4x^3+3x^2+c_1` `f(x)=intf'(x)dx`...

Asked by enotes on via web

• Math
`f''(x)=x^6-4x^4+x+1` `f'(x)=intf''(x)dx` `f'(x)=int(x^6-4x^4+x+1)dx` `f'(x)=x^7/7-4(x^5/5)+x^2/2+x+c_1` `f'(x)=x^7/7-(4x^5)/5+x^2/2+x+c_1` `f(x)=intf'(x)dx`...

Asked by enotes on via web

• Math
`f(x) = x - 3` To find the general antiderivative of this function, we take its integral. `F(x) = int f(x) dx = int(x-3)dx` Take the integral of each term. `=intxdx - int3dx` For the first...

Asked by enotes on via web

• Math
You need to evaluate the most antiderivative of the function, such that: `int f(x) dx = F(x) + c` `int ((1/2)x^2 - 2x + 6) dx = int(1/2)x^2 dx - int 2xdx+ int 6 dx` `int ((1/2)x^2 - 2x + 6) dx =...

Asked by enotes on via web

• Math
`f(x)=1/2+3/4x^2-4/5x^3 ` To determine the most general antiderivative of this function, take the integral of f(x). `F(x)=intf(x) dx= int(1/2+3/4x^2-4/5x^3)dx` Then, apply the integral formula `int...

Asked by enotes on via web

• Math
You need to evaluate the most antiderivative of the function, such that: `int f(x) dx = F(x) + c` `int (8x^9 - 3x^6 + 12x^3) dx = int8x^9 dx - int 3x^6dx+ int12x^3 dx` `int (8x^9 - 3x^6 + 12x^3) dx...

Asked by enotes on via web

• Math
First, you need to open the brackets, such that: `f(x) = (x+1)(2x-1) = 2x^2 + x - 1` You need to evaluate the most antiderivative of the function, such that: `int f(x) dx = F(x) + c` `int (2x^2 + x...

Asked by enotes on via web

• Math
You need to evaluate the most general antiderivative, using the following rule, such that: `int f(x) dx = F(x) + c` First, you need to open the brackets, such that: `f(x) = x(2-x)^2 = x*(4 - 4x +...

Asked by enotes on via web

• Math
The most general antiderivative F(x) of the function f(x) can be found using the following relation: `int f(x)dx = F(x) + c` `int (7x^(2/5) + 8x^(-4/5))dx = int (7x^(2/5))dx + int (8x^(-4/5))dx`...

Asked by enotes on via web

• Math
The most general antiderivative F(x) of the function f(x) can be found using the following relation: `int f(x)dx = F(x) + c` `int (x^(3.4) - 2x^(sqrt2 - 1))dx = int (x^(3.4))dx - int (2x^(sqrt2 -...

Asked by enotes on via web

• Math
The answer is `F(x) = x*sqrt(2) + C,` where C is any constant. Let's check: `F'(x) = (x*sqrt(2) + C)' = x'*sqrt(2) + 0 = 1*sqrt(2) = sqrt(2),` QED.

Asked by enotes on via web

• Math
`e^2` isn't depend on x, so its antiderivative is `x*e^2.` The general antiderivative is `x*e^2+C,` where C is any constant. Let's check: `(x*e^2+C)'=x'*e^2+C'=1*e^2+0=e^2.`

Asked by enotes on via web

• Math
The most general antiderivative F(x) of the function f(x) can be found using the following relation: `int f(x)dx = F(x) + c` `int (3sqrt x - 2root(3) x)dx = int (3sqrt x)dx - int (2root(3) x)dx`...

Asked by enotes on via web

• Math
`f(x)= root(3)(x^2) + xsqrtx` To determine the most general antiderivative of this function, take the integral of f(x). `F(x) = intf(x) dx = int (root(3)(x^2)+xsqrtx)dx` Express the radicals in...

Asked by enotes on via web

• Math
Hello! At first, consider line graph. It gives the same information as the bar graph, but line graph combines data from both cities which makes comparing easier. From the line graph we see those...

Asked by user5345646 on via web

• Math

Asked by user4416978 on via web

• Math
There are an infinite number of values on the number line between `1/3` and ```1/4` .`` One way to find a value between is to write equivalent fractions using a common denominator. Because the...

Asked by alyssavela704 on via web

• Math
Hello! When two points of the straight line are given, the slope of this line is `(y_2-y_1)/(x_2-x_1).` Here this is equal to `(-2-8)/(r-6) = -10/(r-6)` and must be 1. So `-10/(r-6)=1,` r-6=-10,...

Asked by debgray3676 on via web

• Math
Hello! Exponential growth function has a form `y=A*(1+r)^x,` where A is the initial value and r is the growth rate. If we substitute x=0 we obtain `y(0)=A*(1+r)^0=A.` Recall that y-intercept is the...

Asked by user7485737 on via web

• Math
The question is based on the similarity of triangles. In similar triangles ratio of the corresponding sides is same. So let's find the scale factor Scale factor=2/1.5 = 1.33 So,...

Asked by nivlac36 on via web

• Math
The y-intercept of a graph of the function is the y-coordinate of the point where the graph intersects y-axis. The x-coordinate of this point is 0. Therefore, to find the y-intercept, plug in x = 0...

Asked by ravennybae on via web

• Math
Hello! Let's denote the number of minivans washed as m and the number of cars as c. Then she earned 7m dollars for minivans and 4c for cars. It is given that `7m+4c=41.` If m and c could be...

Asked by emilys91612 on via web